Monsignor Lynch is honored by parish (Raton Range Raton, New Mexico, 1978)
Newspaper article on the gathering to honor Rev. Monsignor Thomas J. Lynch.
Master list item #: 25
File location is in the Raton File Cabinet
Keywords: Lynch, Thomas J; Sanchez, Robert F; Lynch, William B; Weber, Josephy; Hogan, Thomas J; Donelan, Edward; Greigo, J. Sabine; Klister, Irving F; Carroll, Gregory; Moore, Augustine J; Hammer, Carl L; Stadtmueller, Fred; Montoya, Louis; Weber, Joseph; Marren, Mary; Adelina, Mary; Sonchar, Victor (Mrs.); Scheafer, Bob; Caldarelli, Pete; Caldarelli, Esther; Carnevale, Anthony; Carnevale, Mary Jean; Carnevale, Elaine; St. Patrick's Church; Holy Trinity Church; Mercy Medical Center; Raton Catholic School; St. Patrick's Parish; Kights of Columbus; The Alter and Rosary Society; Catholic Daughters of America; Local History; Life and Customs; Churches; Celebration; Ordination; Pastor; Raton, New Mexico; Santa Fe, New Mexico; Palos Heights, Illinois; Las Vegas, New Mexico; Springer, New Mexico; Trinidad, Colorado; Durango, Colorado